How Far the Digital Marketing Innovation done by Natural Raw Material MSMEs during the Pandemic? Case of Magelang Region, Central Java Region, Indonesia - Hironimus Leong; Berta Bekti Retnawati; B. Irmawati (Journal of Social Entrepreneurship Theory and Practice, 2021)
There are various steps taken by Natural Raw Materials MSMEs in Magelang Region in facing the economic downturn during the pandemic for their business continuity. The effort to adapt to the difficulties during the pandemic period is by utilizing information technology to encourage the economy to continue growing and developing. The use of social media and e-commerce is an example of marketing adaptation from a traditional form to a more modern model. Participation in virtual exhibitions is also another example of how MSMEs adopt digital transformation. The study aims to determine how far the natural raw material MSMEs actors can utilize the digital marketing during the pandemic and prepare for the adaptation in the new normal period. This study uses a qualitative descriptive approach involving 30 MSMEs. The result shows that MSMEs who are transitioning away from traditional marketing techniques and attempting to be innovative in response to environmental changes have a chance to sustain themselves. Marketing via e-commerce, social media, and virtual product introduction can help to increase markets and enhance the economy. Those that are not prepared for the adaption process, on the other hand, will choose to operate other businesses or even close them.